Observation of Grease Fluidity in a Ball Bearing Using Neutron Imaging Technology - Kazumi Sakai; Yusuke Ayame; Yoshimu Iwanami; Nobuharu Kimura; Yoshihiro Matsumoto (Tribology Online, 2021)
The grease fluidity and migration inside a ball bearing has been visualized non-destructively by using a neutron imaging technology. It has been clarified that a lithium (Li) complex grease with lower torque lubricates in the channeling state and that a single Li soap grease with higher torque lubricates in the churning state. Adhesion of the Li complex grease to bearing balls was quite limited, and most of the grease stayed on cage surfaces between the balls; adhesion of the single Li soap grease to bearing balls was remarkable. These observation results correlate to their grease performances for the bearing torque. The less adhesion of the Li complex grease to bearing balls contributes to reducing bearing torque due to easy rotations of bearing balls. In contrast, the remarkable adhesion of the single Li soap grease causes higher shear resistance for bearing ball rotations. The neutron imaging technology clarified the mechanism of the bearing torque difference depending on the grease types and could contribute to developments of energy-saving greases.